Activation of the TLR4 signaling pathway and abnormal cholesterol efflux lead to emphysema in ApoE-deficient mice - Goldklang, Monica (American Physiological Society, 2012)
Smokers with airflow obstruction have an increased risk of atherosclerosis, but the relationship between the pathogenesis of these diseases is not well understood. To determine whether hypercholesterolemia alters lung inflammation and emphysema formation, we examined the lung phenotype of two hypercholesterolemic murine models of atherosclerosis at baseline and on a high-fat diet. Airspace enlargement developed in the lungs of apolipoprotein E-deficient (Apoe(−/−)) mice exposed to a Western-type diet for 10 wk. An elevated number of macrophages and lymphocytes accompanied by an increase in matrix metalloproteinase-9 (MMP-9) activity and MMP-12 expression was observed in the lungs of Apoe(−/−) mice on a Western-type diet. In contrast, low-density lipoprotein receptor-deficient (Ldlr(−/−)) mice did not exhibit lung destruction or inflammatory changes. Most importantly, we revealed augmented expression of the downstream targets of the Toll-like receptor (TLR) pathway, interleukin-1 receptor-associated kinase 1, and granulocyte colony-stimulating factor, in the lungs of Apoe(−/−) mice fed with a Western-type diet. In addition, we demonstrated overexpression of MMP-9 in Apoe(−/−) macrophages treated with TLR4 ligand, augmented with the addition of oxidized LDL, suggesting that emphysema in these mice results from the activation of the TLR pathway secondary to known abnormal cholesterol efflux. Our findings indicate that, in Apoe(−/−) mice fed with an atherogenic diet, abnormal cholesterol efflux leads to increased systemic inflammation with subsequent lung damage and emphysema formation.